Effect of functionalization of activated carbon on the efficacy of lipase in the production of biodiesel from Moringa oleifera oil - Abia Kadouf, Yara Hunud; Ahmed Kabbashi, Nassereldin; Alam, Md. Zahangir; Mirghani, Mohamed Elwathig Saeed (Kulliyah of Engineering, International Islamic University Malaysia, 2016)

(untitled)
Biodiesel has become one of the leading options to replace fossil fuels as a source of energy. Current methods of producing biodiesel generate toxic waste as a result of chemical catalysts used to accelerate the process. Consequentially, this waste requires expensive treatment before being safely released to the environment. In order to reduce downstream processing costs and to ensure resource conservation, a more environmentally friendly approach is required. Hence, this study has elected to explore the efficacy of modified activated carbon in enhancing the activity of Candida antarctica lipase as a catalyst in the production of biodiesel from Moringa oleifera. Moringa oil will be extracted using Soxhlet extraction, with hexane as the solvent of choice. The crude oil was then characterized with respect to its physic-chemical properties namely its acid value, iodine value, density, moisture content, viscosity and saponification value. The properties of the oil were found to be within the appropriate standards for a good biodiesel feedstock oil. Candida antarctica lipase was then purified and immobilized on modified activated carbon in order to enhance the activity and effectiveness of the enzyme and compared to unmodified activated carbon.